The Communication about Destination Projected Image on Short-form Video Platforms: A Systematic Literature Review - Li, Lei; Jusang Bin Bolong (International Journal of Social Sciences and Public Administration, 2024)
With the continuous innovation of Internet technology, the way of communication is evolving rapidly. Social media enables the creation and dissemination of forms of expression. In today’s environment, short videos play a key role in the dissemination of destination image projection, and it is particularly important to build and maintain the virtual image of the destination. This paper systematically reviews the relevant literature and comprehensively analyzes the research on destination image projection in short videos. In the past decade, the relevant research results have steadily increased, covering multiple tourism destinations and platforms. This study includes articles from English peer-reviewed academic journals and discusses them by topic. Through the literature review, this paper explores the direction of current research and outlines future research trends.